2012
DOI: 10.5993/ajhb.36.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk and Quitting Behaviors: Results From the ITC 4-Country Survey

Abstract: Objective To rigorously test the relation between perceived risk (ie, belief about the likelihood of harm) and quitting smoking. Methods Data from a longitudinal study with a nonrestrictive sample of smokers (N = 4307) from the United States, Canada, the United Kingdom, and Australia were examined to predict quitting behaviors at 8–12 months. Results Perceived risk predicted plans to quit, quit attempts, and, to some extent, sustained quitting. The relation was stronger for relatively simple (eg, plans to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…(Montgomery et al, 2003) People with a family member or friend with diabetes have also reported greater concern about diabetes and its complications. (Mani et al, 2011) Perceived risk is a component of behavioral activation and contemplating behavior changes(Costello et al, 2012; Larsman et al, 2012; Lyna et al, 2002) and may encourage adoption of preventive behaviors such as physical activity, at least in the short-term. (Chang et al, 2011; Mani et al, 2011; Montgomery et al, 2003) Diabetes interventions engaging couples have reported that couples can achieve reductions in caloric intake and increases in physical activity together.…”
Section: Discussionmentioning
confidence: 99%
“…(Montgomery et al, 2003) People with a family member or friend with diabetes have also reported greater concern about diabetes and its complications. (Mani et al, 2011) Perceived risk is a component of behavioral activation and contemplating behavior changes(Costello et al, 2012; Larsman et al, 2012; Lyna et al, 2002) and may encourage adoption of preventive behaviors such as physical activity, at least in the short-term. (Chang et al, 2011; Mani et al, 2011; Montgomery et al, 2003) Diabetes interventions engaging couples have reported that couples can achieve reductions in caloric intake and increases in physical activity together.…”
Section: Discussionmentioning
confidence: 99%
“…First are worries or concerns about health (Costello, Logel, Fong, Zanna, & McDonald, 2012; Emery et al, 2013; International Agency for Research on Cancer, 2008) which are theorised to increase people’s interest in quitting smoking. Second are functional beliefs about the utility of smoking (Yong & Borland, 2008), which should be negatively related to quitting activity.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that these beliefs can affect smoking behavior, although not consistently. For example, concern about the health consequences of smoking motivates many smokers to try to quit (Costello et al, 2012), and some smokers switched to “light” cigarettes because they believed these were healthier than non-light cigarettes (Cummings et al, 2004). However, across multiple prospective studies, the stated reason for wanting to quit smoking (i.e., health concerns versus other concerns) was rarely related to success in quitting (McCaul et al, 2006).…”
Section: Introductionmentioning
confidence: 99%